How well does shear wave elastography predict elevated filling pressures? a comparison to the current guideline algorithm. (4th February 2022) - Werner, AE; Bezy, S; Orlowska, M; Kobiak, G; Duchenne, J; Ingram, M; Desmet, W; Mccutcheon, K; Delcroix, M; Van Cleemput, J; Ince, H; D"hooge, J; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): University Hospitals (Uz) Leuven Background: The assessment of left ventricular diastolic function is complex, as there is no single invasive parameter that provides a direct measurement of myocardial compliance, myocardial relaxation, or – as a surrogate - LV filling pressure. A combination of several parameters is therefore used to estimate the diastolic function. Shear wave (SW) elastography is a novel method based on high frame rate echocardiography. SWs occur after mechanical excitation of the myocardium, e.g. after mitral valve closure (MVC), and their propagation velocity is directly related to myocardial stiffness (MS). The propagation velocity of SWs is directly related to myocardial stiffness and could be used for estimating left ventricular diastolic pressures. Purpose: The aim of this study was to investigate if the MS at mid-diastole or end-diastole and the velocities of natural shear waves are related and, thus, could be used to estimate left ventricular end-diastolic pressures (LVEDP) as marker of diastolic function. Methods: We prospectively enrolled 70 patients with a wide range of diastolic function, scheduled for heart catheterization so that LV mid diastolic filling pressures (LVMDP) and enddiastolic filling pressures (LVEDP) could be invasively measured (Panel B). Patients with dysfunction in the anteroseptal wall or regional myocardial abnormalities, as well as severe aortic stenosis, and a more than moderate mitral regurgitation were excluded. Echocardiography was performed immediately after catheterization. SW elastography in parasternal long axis views of the left ventricle (LV) was performed using an experimental scanner (HD-PULSE) at 1050 ± 220 frames per second. Tissue acceleration maps were extracted from an anatomical M-mode line along the midline of the LV septum. The SW propagation velocity at MVC was measured as the slope on the M-mode acceleration map (Panel A). Standard echocardiographic parameters of diastolic function were obtained with a high end ultrasound machine. The Algorithm for evaluating diastolic dysfunction as recommended by the European Association of Cardiovascular Imaging Guidelines 2016 was used for estimating LVMDP. Results: SW Velocity correlated better with LVMDP (AUC = 0.8, Sensitivity = 0.84, Specificity= 0.80; =0.26; Panels C, E) than the Guideline approach (AUC = 0.67, Sensitivity = 0.33, Specificity = 1.00, Panel G). SWV showed the best results in predicting LVEDP (AUC = 0.94, Sensitivity = 0.92, Specificity = 0.89 and =0.56 (Panels D, F)). Conclusions: Shear wave velocities, detected by high frame rate elastography, have a strong correlation with the end-diastolic filling pressure and allowed significantly better to differentiate normal from elevated filling pressure that current guideline recommended algorithms. This suggests a potential clinical value of the new method for the non-invasive assessment of diastolic function.